Analisis Dinamika Inflasi Dan Pengangguran Di Indonesia Berdasarkan Teori Kurva Phillips - Hidayati, Amalia Nuril; Puspa Sa'adah, Beryl Claresta; Firnanda, Denta Khrisna; Setyo Ningrum, Lisa Selviani; Azizah, Nur (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the relationship between inflation and unemployment in Indonesia using the Phillips Curve theory approach. Inflation and unemployment are two important indicators of macroeconomic stability, and the Phillips Curve theory states that there is a trade-off between the two. This research uses a library research method with an analytical descriptive and interpretative approach, based on academic literature as well as the latest macroeconomic data from the Central Bureau of Statistics (BPS). The results show that the negative relationship between inflation and unemployment as explained in the Phillips Curve does not fully apply in the Indonesian context. Recent data shows a simultaneous decline in both inflation and unemployment, which contradicts the classical theory and indicates a “flattening of the Phillips Curve” phenomenon. This finding suggests the need for a more comprehensive and contextualized approach to economic policy in understanding Indonesia's macroeconomic dynamics. Therefore, the Phillips Curve remains an important initial reference, but its application needs to consider the dynamics of the Indonesian economy which is influenced by structural and external factors.